Definition of a clinical strategy to enhance the efficacy, efficiency and safety of egg donation cycles with imported vitrified oocytes. Issue 4 (2nd April 2020) - Rienzi, Laura; Cimadomo, Danilo; Maggiulli, Roberta; Vaiarelli, Alberto; Dusi, Ludovica; Buffo, Laura; Amendola, Maria Giulia; Colamaria, Silvia; Giuliani, Maddalena; Bruno, Giulietta; Stoppa, Marta; Ubaldi, Filippo Maria
Abstract: STUDY QUESTION: Which is the most suitable clinical strategy in egg donation IVF cycles conducted with imported donated vitrified oocytes? SUMMARY ANSWER: The importation, and allocation, of at least eight vitrified eggs per couple during an egg donation cycle is associated with a high cumulative live birth delivery rate per cycle, as well as the confident adoption of a single blastocyst transfer strategy to minimize the risk of multiple pregnancies. WHAT IS KNOWN ALREADY: IVF using donor eggs is commonly used worldwide to treat women who are unable to conceive with their own oocytes. In 2014, the Constitutional Court (n.162/2014) gave permission for gamete donation to be allowed for ART in Italy. Initially recommended as a therapeutic approach for premature ovarian insufficiency, the use of donated oocytes has become more and more common. In countries such as Italy, fresh oocyte donation is theoretically possible, but practically impossible due to the lack of donors. In fact, the Italian law does not allow reimbursement to the young women, who can only voluntarily donate their eggs. Therefore, Italian IVF centers have established several collaborations with international oocyte cryo-banks. The most popular workflow involves the importation of donated oocytes that have been vitrified. However, recent evidence has questioned the overall efficacy of such an approach. This is because detrimental effects arising from oocyte vitrification and warming might reduce the number of eggs available for insemination, with a consequential reduction in the achievable live birth rate per cycle. STUDY DESIGN, SIZE, DURATION: This was a longitudinal cohort study, conducted between October 2015 and December 2018 at two private IVF centers. Overall, 273 couples were treated (mean maternal age: 42.5 ± 3.5 years, range: 31–50 years; mean donor age: 25.7 ± 4.2, 20–35 years) with oocytes purchased from three different Spanish egg banks. PARTICIPANTS/MATERIALS, SETTING, METHODS: We performed an overall analysis, as well as several sub-analyses clustering the data according to the year of treatment (2015–2016, 2017 or 2018), the number of warmed (6, 7, 8 or 9) and surviving oocytes (≤4, 5, 6, 7, 8 or 9) and the cycle strategy adopted (cleavage stage embryo transfer and vitrification, cleavage stage embryo transfer and blastocyst vitrification, blastocyst stage embryo transfer and vitrification). This study aimed to create a workflow to maximize IVF efficacy, efficiency, and safety, during egg donation cycles with imported vitrified oocytes. The primary outcome was the cumulative live birth delivery rate among completed cycles (i.e. cycles where at least a delivery of a live birth was achieved, or no embryo was produced/left to transfer). All cycles, along with their embryological, obstetric and neonatal outcomes, were registered and inspected. MAIN RESULTS AND THE ROLE OF CHANCE: The survival rate after warming was 86 ± 16%. When 6, 7, 8 and 9 oocytes were warmed, 94, 100, 72 and 70% of cycles were completed, resulting in 35, 44, 69 and 59% cumulative live birth delivery rates per completed cycle, respectively. When ≤4, 5, 6, 7, 8 and 9 oocytes survived, 98, 94, 85, 84, 66 and 68% of cycles were completed, resulting in 16, 46, 50, 61, 76 and 60% cumulative live birth delivery rates per completed cycle, respectively. When correcting for donor age, and oocyte bank, in a multivariate logistic regression analysis, warming eight to nine oocytes resulted in an odds ratio (OR) of 2.5 (95% CI: 1.07–6.03, P = 0.03) for the cumulative live birth delivery rate per completed cycle with respect to six to seven oocytes. Similarly, when seven to nine oocytes survived warming, the OR was 2.7 (95% CI: 1.28–5.71, P < 0.01) with respect to ≤6 oocytes. When cleavage stage embryos were transferred, a single embryo transfer strategy was adopted in 17% of cases ( N = 28/162); the live birth delivery rate per transfer was 26% ( n = 43/162), but among the pregnancies to term, 28% involved twins ( n = 12/43). Conversely, when blastocysts were transferred, a single embryo transfer strategy was adopted in 96% of cases ( n = 224/234) with a 30% live birth delivery rate per transfer ( N = 70/234), and the pregnancies to term were all singleton ( n = 70/70). During the study period, 125 babies were born from 113 patients. When comparing the obstetric outcomes for the cleavage and blastocyst stage transfer strategies, the only significant difference was the prevalence of low birthweight: 34 versus 5%, respectively ( P < 0.01). However, several significant differences were identified when comparing singleton with twin pregnancies; in fact, the latter resulted in a generally lower birthweight (mean ± SD: 3048 ± 566 g versus 2271 ± 247 g, P < 0.01), a significantly shorter gestation (38 ± 2 versus 36 ± 2 weeks, P < 0.01), solely Caesarean sections (72 versus 100%, P = 0.02), a higher prevalence of low birthweight (8 versus 86%, P < 0.01), small newborns for gestational age (24 versus 57%, P = 0.02) and preterm births (25 versus 86%, P < 0.01). LIMITATIONS, REASONS FOR CAUTION: This retrospective study should now be confirmed across several IVF centers and with a greater sample size in order to improve the accuracy of the sub-analyses. WIDER IMPLICATIONS OF THE FINDINGS: Single blastocyst transfer is the most suitable approach to achieve high success rates per procedure, thereby also limiting the obstetric complications that arise from twin pregnancies in oocyte donation programs. In this regard, the larger the cohort of imported donated vitrified oocytes, the more efficient the management of each cycle. STUDY FUNDING/COMPETING INTEREST(S): None. TRIAL REGISTRATION NUMBER: None.